The relationship between children's temperament and fundamental movement skills mediated by autonomy and self-regulation. Issue 8 (11th June 2022) - Jang, Yujin; Hong, Yea-Ji
ABSTRACT: This study examined two subfactors of fundamental movement skills: locomotion skills and object-control skills. The direct and indirect effects of children's temperament on fundamental movement skills and the mediating effects of autonomy and self-regulation were examined. Participants included 278 pairs of 3- to 5-year-old children and their mothers from 4 day care centres. High levels of emotionality and sociability were positively associated with a high level of children's autonomy, self-regulation and fundamental movement skills. There was a mediating effect of children's autonomy and self-regulation on the effect of temperament on locomotion skills, but there was no mediating effect on object-control skills. The results provide empirical evidence of holistic development by confirming that temperament is a variable that affects gross motor development and that children's psychological development is related to motor development.